2023
DOI: 10.3390/admsci13040111
|View full text |Cite
|
Sign up to set email alerts
|

Women Entrepreneurship: Challenges and Perspectives of an Emerging Economy

Abstract: Women entrepreneurship is considered by many researchers as an imminent phenomenon of the 21st century, especially for developing countries. Due to its contribution to the economy and society, recent studies have focused on investigating its motivational factors, as well as achievements. Moreover, researchers have come up with different entrepreneurial perspectives in different societies and cultures and have called for further analysis. In this context, the main purpose of this research was to assess the driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…They highlighted the first-hand insight women entrepreneurs possess regarding the challenges faced by women and the potential impact of increasing the number of women entrepreneurs in South Africa on unemployment and poverty alleviation. In their businesses, women provide many new jobs, reinvest most of their profits in the family, work for it, are more sensitive to the social issues that they face, and can reduce poverty by contributing to economic growth by creating new jobs and increasing the income of poor people (Bardhyl, Kruja & Hysa, 2023). Moreover, entrepreneurship is an important driver behind poverty alleviation and human development (Sutter et al, 2019).…”
Section: Theme 3: Self-reliancementioning
confidence: 99%
“…They highlighted the first-hand insight women entrepreneurs possess regarding the challenges faced by women and the potential impact of increasing the number of women entrepreneurs in South Africa on unemployment and poverty alleviation. In their businesses, women provide many new jobs, reinvest most of their profits in the family, work for it, are more sensitive to the social issues that they face, and can reduce poverty by contributing to economic growth by creating new jobs and increasing the income of poor people (Bardhyl, Kruja & Hysa, 2023). Moreover, entrepreneurship is an important driver behind poverty alleviation and human development (Sutter et al, 2019).…”
Section: Theme 3: Self-reliancementioning
confidence: 99%
“…The findings of the study revealed that the following factors were important for women entrepreneurs in establishing their own business: Women entrepreneurs need to have a strong belief in their own abilities and capabilities in order to be successful; The support of family and friends is essential for women entrepreneurs, as they can provide emotional and financial support; Women entrepreneurs often face challenges in accessing finance, which can make it difficult to start and grow their businesses and Government policies and regulations can either help or hinder women entrepreneurs, so it is important to have favourable policies in place. Akter and Nishat, (2023) examined the challenges and perspectives of women entrepreneurs in an emerging economy. The study used a qualitative research approach and collected data from 20 women entrepreneurs through in-depth interviews.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The study conducted by Morshed & Haques, (2015) [4] observed that the women entrepreneurs have more social mobility power than that of housewives and the enterprise owned women are more empowered than the housewives. The study highlighted by Ahmetaj et al, (2023) [1] that Banks can also act as a mediatory element in promoting women entrepreneurship by providing facilities for females applying for loans.…”
Section: Introductionmentioning
confidence: 99%